2010
DOI: 10.1016/j.virol.2010.08.016
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of Rift Valley fever virus in the mouse model

Abstract: Detailed studies describing the pathogenesis of Rift Valley fever (RVF) virus (RVFV) in the mouse model are lacking. A fully characterized small animal model of RVF is needed to evaluate potential vaccines and therapeutics. In this study, we characterized the pathogenesis of RVFV throughout the disease course in mice. Infection produced high-titer viremia and demonstrated RVFV tropism for a variety of tissue and individual cell types. Overwhelming infection of hepatocytes, accompanied by apoptosis, was a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
168
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(211 citation statements)
references
References 20 publications
39
168
4
Order By: Relevance
“…To explain the host-wide effect of localized VRP RVF immunization, we hypothesize that immunization results in VRP RVF infection of resident macrophages or dendritic cells in the skin. Recent work has demonstrated that macrophages and dendritic cells are permissive to replication and are important targets of RVFV infection (28,30,34). Given the absence of the NSs protein in the VRP RVF construct, active replication within these cell types should stimulate a strong IFN response, as shown in vitro (30), leading to a systemic antiviral response.…”
Section: Discussionmentioning
confidence: 98%
“…To explain the host-wide effect of localized VRP RVF immunization, we hypothesize that immunization results in VRP RVF infection of resident macrophages or dendritic cells in the skin. Recent work has demonstrated that macrophages and dendritic cells are permissive to replication and are important targets of RVFV infection (28,30,34). Given the absence of the NSs protein in the VRP RVF construct, active replication within these cell types should stimulate a strong IFN response, as shown in vitro (30), leading to a systemic antiviral response.…”
Section: Discussionmentioning
confidence: 98%
“…Studies using Chikungunya and human immunodeficiency virus as well as haemorrhagic fever viruses such as Ebola Zaire and RVFV demonstrated that viruses can replicate in macrophages (Bol et al, 2011a(Bol et al, , 2011bBray & Geisbert, 2005;DupuisMaguiraga et al, 2012;Lewis et al, 1987;McElroy & Nichol, 2012). Kupffer cells, resident liver macrophages, as well as circulating white blood cells have been shown to stain positive for RVFV antigen after infection (Kamal, 2009;Shieh et al, 2010;Smith et al, 2010) and it is thought that macrophages could support dissemination of the virus from the site of infection to target organs as has been shown with Ebola virus (Bray & Geisbert, 2005). Here, we wanted to characterize the response of primary mouse BMDM cells to infection with either WT or attenuated strains of RVFV and correlate cytokine profiles with regulation of intracellular signalling processes.…”
Section: Introductionmentioning
confidence: 99%
“…The infected Langerhans dendritic cells migrate to draining lymph nodes where a brief viral replication may occur and the virus is considered to enter the blood stream through the lymphatic and thoracic ducts [61]. The virus may enter the bone marrow [62] or liver [63] where a secondary amplification may occur or directly disseminate to the brain inducing inflammation.…”
Section: Pathogenesis Of Arboviral Infectionsmentioning
confidence: 99%
“…Results from RVFV suggest that the liver seems to be an early and dominant target of the virus [63]. The damage to the hepatocytes of the RVFV-infected liver is likely a result of apoptosis [63].…”
Section: Pathogenesis Of Arboviral Infectionsmentioning
confidence: 99%
See 1 more Smart Citation